Study on the Design Path of Immersive Digital Resources for Museum Education from the Perspective of Situated Learning - Dong, Hao; Du, Yifan (Journal of Educational Research and Policies, 2025)
Against the backdrop of the digital transformation of museum education and the rapid development of immersive technologies, this study focuses on the actual role of immersive digital resources in the learning processes of children and adolescents. Although immersive environments possess strong experiential attributes, their educational effectiveness fundamentally depends on how learners perceive, act, and construct understanding within specific learning situations. Therefore, it is necessary to re-examine the design logic of immersive resources from the perspective of learning theory. Anchored in situated learning theory, this study adopts a methodology combining literature review, multi-case analysis, and conceptual synthesis to explore the key elements that shape immersive digital resources in terms of learning-context construction, task-structure arrangement, and interaction-mechanism design. The study proposes an immersive learning design framework that is context-based, action-driven, and feedback-supported, thereby explaining how immersive technologies facilitate learners’ meaning-making during experiential engagement. The findings provide theoretical reference for museums seeking to develop educational immersive resources under digitalization, and offer practical directions for optimizing instructional design in related applications.